Obhajanje zakramenta svete birme in njeni teološki ter liturgično-glasbeni vidiki - Oblonšek, Cecilija (Edinost in dialog, 2025)
This article posits that due to specific emphases in our pastoral practice in the context of the sacrament of confirmation, the theology of this sacrament is characterised by a certain uncertainty, which engenders a blurred understanding of the logic of receiving the sacraments of initiation. The Eucharist should be the culmination and goal of the »initiation« period, while Confirmation is one of the sacraments of initiation and not a sacrament of service, as it is subconsciously perceived in our environment. In this awareness, the primary consideration has been the celebration of the sacrament of confirmation within the Mass, which has the capacity to either affirm or diminish the significance of the sacrament in our pastoral practice. The role of liturgical music in a ceremonial context is twofold: firstly, it contributes to the solemnity of the event, and secondly, it provides an opportunity to present the key emphases of the Holy Spirit's work to the confirmands through the medium of sung liturgy. In addition, it serves to introduce them to the precious musical treasures of the universal Church, and to enable them to enter adult faith.
Keywords: birma; choral singing; confirmation; inculturation; inkulturacija; koralni spevi; liturgical music; liturgična glasba; sacraments; zakramenti